Brand positioning of the university as strategic guidelines for integration in the international educational space - Karamyshev, Dmytro; Hordiienko, Liudmyla (Public Administration and Regional Development, 2023)
The article highlights the issue of ranking evaluation of universities, which is an indicator of their academic reputation in the context of integration into the international and European space of higher education. Conceptual principles and methodological approaches regarding the rating evaluation of the results of higher education institutions and their improvement, as well as the forms and means of branding and positioning of universities were substantiated. It is noted that the proper positioning of leading Ukrainian universities in global rankings and their promotion to international performance evaluation systems will open up additional opportunities for graduates of competitive educational programs to implement acquired competencies, and for scientific and pedagogical staff to demonstrate professional knowledge on the international labor market. Emphasis is placed on the use of a specific indicator, namely the sectoral Index of the evaluation of the activities of higher education institutions, which can be a universal indicator for evaluating the quality of educational activities in the field of higher education within a certain field of knowledge. The introduction of specific branch and subject indicators for evaluating the activities of higher education institutions will provide an opportunity to optimize the evaluation system and improve the quality of the university's positioning, bringing it closer to the appropriate target audience. The key integrative components of proactive branding of universities have been determined, which must be ensured in the target categories of stakeholders, based on the key areas of optimization, among which it is proposed to identify as priority three integration components of branding and positioning of the university, namely web resources, place of stakeholders, processes of internationalization.